(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article deals with the methods of using interactive whiteboards in teaching English verb vocabulary. If these methods are used effectively, the students of this class will have fully mastered the vocabulary of the English language, which will eliminate possible shortcomings in oral and written speech.